2018
DOI: 10.1017/s1751731117002129
|View full text |Cite
|
Sign up to set email alerts
|

Active immunization against GnRH in pre-pubertal domestic mammals: testicular morphometry, histopathology and endocrine responses in rabbits, guinea pigs and ram lambs

Abstract: Effective tools for male contraception are important in the control of reproduction in animal populations. The aim of the present study was to evaluate the effects of active immunization against gonadotropin-releasing hormone (GnRH) on male reproductive function assessing testicular morphological changes and serum-gonadotropin levels in pre-pubertal rabbits, guinea pigs and ram lambs. An anti-GnRH vaccine was developed by linking a GnRH-homologous molecule to a tetanus clostridial toxoid (Al(OH)3 coadjuvant). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…Thus, the onset of spermatogenesis is characterized by an increase in germ cell (GCs) numbers [14,6], representing a gradual and complex activation of sets of differentiation genes. The study of the prepubertal period and the role of different spermatogenic factors involved is important for the prediction of future reproductive performance in adult males, with the goal of better impacting the reproductive management of farm animals [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the onset of spermatogenesis is characterized by an increase in germ cell (GCs) numbers [14,6], representing a gradual and complex activation of sets of differentiation genes. The study of the prepubertal period and the role of different spermatogenic factors involved is important for the prediction of future reproductive performance in adult males, with the goal of better impacting the reproductive management of farm animals [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…Lents et al (2018) found azoospermia of 83.33% in goats immunocastrated with 1.0 and 0.5 mL of Bopriva. Aponte et al (2018) evaluated the effects of active anti-GnRH immunization on the reproductive function of lambs and observed that spermatozoa were not found in 60% of the transverse sections of seminiferous tubules in the immunized group. Ferro et al (2004) also used an anti-GnRH vaccine in adult sheep, which had active spermatozoa in only 19% to 28% of the tubules in immunized animals, compared with the untreated group.…”
Section: Seminal Fluid Production and Qualitymentioning
confidence: 99%
“…Immunocastration has been proven to be effective, and several specific vaccines are available on the market for swine (Dunshea et al, 2001;Zeng et al, 2002) and bovines (Amatayakul-Chantler et al, 2013;Pérez-Linares et al, 2017). Although anti-GnRH vaccines have already been studied in ovine (Han et al, 2015;Aponte et al, 2018) and caprine species (Lents et al, 2018), there is still no specific vaccine for these species on the market, and a vaccination protocol is lacking.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…GnRH is a wellstudied target in animal immunocontraception with continuing interest. [5][6][7] Given that GnRH is a small (10 amino acids) 'self' protein, it requires conjugation to a larger carrier protein for increased antigenicity. Most of the GnRH-based vaccines are chemical conjugates of multiple GnRH copies with carrier proteins such as tetanus toxoid, 8 diphtheria toxoid, 9 keyhole limpet hemocyanin, 10 Concholepas concholepas hemocyanin (blue protein) 4 or ovalbumin.…”
Section: Introductionmentioning
confidence: 99%